Karakteristik Formasi Seblat di Daerah Bengkulu Selatan - Heryanto, Rahmat (Pusat Survei Geologi, 2006)
The Seblat Formation is an oldest Tertiary sedimentary rock in Bengkulu Basin, which was made up of a clastic sedimentary rocks and were deposited in regretion condition. The lower part was deposited in an open sea shelf – fore slope and the upper part in a fore reef - lagoon shelf environment. The sandstones of formation consist of arkose, litharkose, felspathic litarenite, and litarenite. The framework of grains comprises quartz, feldspar, and rock fragments. Matrix/cement consists of clay and calcareous clay. Accesories mineral are muscovite, epidote, and glouconite. Clasts which formed the sandstone were probably derived from a magmatic arc and recycled orogen of the Pre-Tertary Gumai- Garba Zone. Diagenetic processes recognized are compaction and the formation of authigenic minerals and secondary porosities. Their diagenetic stage were included in the mesogenetic mature A, which equivalent to mudrock stage II, with the paleo temperature80º to 95ºC, and the burial thickness of 2 to 3 km. The mudstone within the Seblat Formation indicates an oil source rock, whereas the sandstone and limestoneare good for a reservoir rock. Keywords : Seblat Formation, diagenesis, compaction, authigenic mineral, mesogenetic